Diversity and Distribution of Orthoptera in Kerandangan Nature Tourism Park - Intan Putri Yasa; Mohammad Liwa Ilhamdi; Eni Suyantri (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Orthoptera is one of the insect orders that has an important role in the ecosystem, acting as herbivores, prey for predators, and decomposition. The study aims to determine the diversity and distribution patterns of Orthoptera in the Kerandangan Nature Tourism Park Area. This research is a descriptive exploratory study and was conducted in November-December 2024. The research method used was pitfall trap and sweep net. Followed by three observation paths: intensive use block, protection block and rehabilitation block. Analysis of species diversity data using the Shannon-Wiener diversity index and calculation of Orthoptera distribution patterns using the Morisita Index. Based on the results of the study, it shows that the Orthoptera found consisted of three families, namely Acrididae, Tettigonidae and Gryllidae, 7 species and 41 individuals. The overall Orthoptera diversity index value (H ') was 1.81 which is included in the moderate category. When ranked based on the diversity index value in each block, the highest diversity was found in the Intensive Utilization Block (H'=1.79) in the medium category, followed by the Protection Block (H'=1.52) in the medium category, and the lowest in the Rehabilitation Block (H'=1.52) in the medium category. Overall, the distribution pattern of Orthoptera individuals in the Kerandangan TWA is generally uniform, with morisita index values ranging from 0.01-0.46 (Id<1).